Network exploration and exploitation capabilities and foreign market knowledge: The enabling and disenabling boundary conditions for international performance - Faroque Anisur; Torkkeli Lasse; Sultana Hafiza; Rahman Mahabubur (Elsevier, 2022)
This empirical study analyzes how strategic orientations influence the relationships between exploration and exploitation-related networking capabilities, foreign market knowledge, and market performance of 198 internationally operating firms in Bangladesh. The results of hierarchical regression showed that a higher level of network exploration capability and network exploitation capability individually generate greater foreign market knowledge. In addition, our results show that international entrepreneurial orientation reinforces the positive effect of network exploration capability.
The positive association between market knowledge and performance, in turn, is accentuated by a proactive export market orientation but attenuated by a responsive export market orientation. These findings suggest that, while both types of networking capabilities are beneficial to develop stocks of foreign market knowledge, firms can acquire and create greater knowledge if they strategically align entrepreneurial orientation with network exploration capability.
Further, to use this market knowledge with the goal of improving their position in international markets, firms need to develop a proactive rather than a responsive export market orientation. The current study contributes to the literature on networking capabilities by analyzing firms' networking capabilities with the lens of exploration-exploitation typologies and incorporating strategic orientations as the contextual factors of such capabilities.